Analisis Rencana Pelaksanaan Pembelajaran (RPP) untuk Implementasi Kurikulum 2013 di Madrasah Tsanawiyah Negeri Binjai - Arlina Arlina; Delvi Sanjuwatma; Nur Awaliyah Afrinda Sari; Juan Adji Rizki (EduInovasi: Journal of Basic Educational Studies, 2023)
The problems faced by teachers in developing lesson plans are that they have not been equipped with KI-1 and KI-2 on indicators and teachers have not revised several lesson plans according to Permendikbud Number 103 of 2014. Therefore this study aims to (1) describe teachers' opinions regarding lesson plans for curriculum implementation 2013, (2) describes the suitability of the contents of lesson plans developed by teachers with the implementation of the 2013 curriculum, (3) describes the constraints faced by teachers in developing lesson plans for implementing the 2013 curriculum, and (4) describes the efforts made by teachers in overcoming problems in developing RPP for implementing the 2013 curriculum. This type of research is descriptive research. The subjects in this study were 3 low grade teachers. Data collection methods used in this study, namely questionnaires, observations and interviews. The collected data was processed using quantitative descriptive analysis techniques and qualitative descriptive analysis. The results showed that (1) the teacher's opinion regarding lesson plans (2) the suitability of the content of lesson plans developed by teachers with the implementation of the 2013 curriculum (3) the obstacles faced by teachers in developing lesson plans were that teachers had difficulty designing learning steps in core activities because they were too much guided to observing, and (4) teacher problems in developing lesson plans can be overcome by filling oneself in by adding insight through workshop activities related to the implementation of the 2013 curriculum, being responsive to information and often sharing information related to the 2013 curriculum with other teachers and with the school principal. Keywords: RPP, curriculum 2013